Effect of anterior nasal packing on middle ear pressure - Bhuiyan, Mohammad Rokanuddin; Ali, Mohammad Idrish; Johora, Fatema; Rumi, Sk Nurul Fattah; Haque, Nazmul; Abdullah, M (Bangladesh Journal of Otorhinolaryngology, 2011)
Objectives: To assess the effect of anterior nasal packing on middle ear pressure. Methods: This cross-sectional study was carried out in the Department of Otolaryngology – Head & Neck surgery, Sir Salimullah Medical College & Mitford Hospital, Dhaka for the period of one year from July 2008 to June 2009. Thirty patients were selected purposively. Results: Thirty patients were studied. Minimum age 14 and maximum age 48 years, 50% patients were 3rd decade, 66.66% were male, male female ratio was 2:1 nasal obstruction was 100% of the patients 30% patients were nasal septum deviation, 30% patients DNS with nasal deformity, 30% patients were underwent septoplasty, 36.66% patients had septoplasty with submucosal diathering 26.66% were endoscopic sinus surgery and 6.66% were septorhinoplasty. The prepack middle ear presurre range from -50 daPa to 0 daPa were maximum followed by 0 daPa to +50 daPa, minimum -65 daPa 4 ears showed presume -100 daPa. Three ears were middle ear pressure between -150 daPa to -100 daPa. 2nd post operatively just before pack removal abnormal middle ear pressure was seen in 26 ears (43.33%) after 5 days abnormal pressure was found in 30 ears. Three ears (75%) out of 4 ears having antrochoanal polyp showed no improvement even five days after pack removed. Conclusion: Chronic nasal obstruction seems to have a detrimental effect on middle ear pressure, which may not return to normal even after removal of chronic obstruction. It appears from this study that there might be some permanent change in peritubal nasopharyngeal mucosa due to chronic nasal obstruction, which needs to be proved histopathologically. Lymphatic stasis at peritubal plexus of lymphatic channels and veins appears to be the causes of lymph oedema following nasal packing. Anterior nasal packing causes reversible negative middle ear pressure which return to normal 5 days after pack removal. Key Words: Anterior nasal pack; middle ear pressure DOI: http://dx.doi.org/10.3329/bjo.v17i2.8853 BJO 2011; 17(2): 125-131